Peranan Ulama Nusantara Abad Ke-18 Dalam Dakwah - Sholeh Fikri (Hikmah, 2018)
This article explains that the Arabic relationship with the archipelago takes place in several phases, the first phase, from the late 8th to 12th centuries in trade relations, the next phase to the end of the fifteenth century. Arab and Persian Muslims whether traders or Sufi travelers, intensify the spread of Islam in various regions of the archipelago. The third stage is from the 16th century until the second half of the seventeenth century, in this period the relationship is more political in addition to religious. The archipelago's relations with the Arab country made some Muslim Nusantara start studying religion to Arab countries especially to Makkah and Madinah, after they learn from the source of Islam religion sebahagiannya settled in Arab land and sebahagiannya da'wah to their respective country, and they all have contribution for the development of da'wah in the archipelago